KERJASAMA INDONESIA DAN INTERPOL DALAM PENANGGULANGAN ILLEGAL, UNREPORTED DAN UNREGULATED FISHING - Aisha Inayati; Reni Windiani (Journal of International Relations Diponegoro, 2019)
This thesis emerges from the phenomenon of cooperation between Indonesia and INTERPOL to tackle IUU fishing in Indonesia from 2015 to 2017. This study aims to analyze why Indonesia collaborates with INTERPOL in tackling IUU Fishing in 2015 - 2017. This research is an explanatory study using qualitative method with data obtained from secondary sources; namely books, journals, reports, and mass media. The scope of this research itself is from 2015 to 2017. For the analysis, this study uses the concept of international norms in constructivists which norms as a standard of behavior could  influence state behavior. The international norm itself in its dissemination through three stages, namely the emergence norms, cascade norms and internationalization are then elaborated to answer the problem formulation in this study. The result of this research  says that the international norm of IUU Fishing as Transanational crime was one of the factors that influenced Indonesia to cooperate with INTERPOL to  tackling IUU fishing.